ACUPUNCTURE FOR COMBATING DELIVERY PAINS IN PRIMIGRAVIDA AND MULTIGRAVIDA WOMEN – A CRITICAL COMPREHENSIVE REVIEW (International Journal of Food and Nutritional Sciences, 2022)
The context: Complementary pain treatment techniques may be more popular than pharmaceutical or invasive options since many women choose non-invasive ways to deal with labour pain. The purpose of this study was to compile the available data about the efficacy of acupuncture in alleviating labour pain. Finding out how well acupuncture works as a pain reliever during labour is the goal of this study. Approach: In order to compile this extensive evaluation, we explored through several databases as well as the lists of references of the research that were considered. Randomised controlled studies (RCTs) of acupuncture including needle insertion for pain during delivery, comparing acupuncture with placebo, no medication or other non-pharmacological means of pain management in childbirth, were included. Regardless of the number of pregnancies (i.e. nulliparous or multiparous) or whether the labour was natural or artificially instigated, we included all women. Within the framework of the research design, we also assessed the quality of the evidences. The results: The randomized controlled trials (RCTs) that were part of already published meta-analyses had different designs, research goals, treatment regimens, and outcome metrics, and they produced mixed findings. In the analysis for systematic review of acupuncture for labour, it may not be suitable to combine these with the assumption of a general conclusion about effectiveness. Additional research is necessary to confirm the positive effects of acupuncture during labour. Conclusion: Acupuncture shows promise in reducing labour discomfort and length, according to moderate evidence. Nonetheless, these results must be confirmed by high-quality research.